Implementasi Digital Marketing pada UMKM Kebab Zannah - Nurhidayah Nurhidayah; Andri Nofiar. Am; Larbiel Hadi (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a significant role in supporting Indonesia's economic growth; however, many still face challenges in utilizing digital technology for marketing activities. Kebab Zannah MSME in Bengkalis Regency primarily relied on word-of-mouth promotion, resulting in limited market reach. This community service program aimed to implement digital marketing strategies to enhance the marketing capacity of Kebab Zannah through the effective use of digital platforms. The program employed a participatory approach consisting of field surveys, needs assessment, SWOT analysis, Segmentation, Targeting, and Positioning (STP) analysis, social media content calendar development, promotional content creation, and Instagram-based marketing implementation. The results demonstrated improved owner capability in managing social media, the development of a more structured digital marketing strategy, stronger brand identity, and the availability of well-planned promotional content. Furthermore, the implementation of digital marketing created greater opportunities to increase product visibility, expand market reach, and strengthen customer engagement. Therefore, digital marketing can be considered an effective strategy for improving MSME competitiveness and supporting sustainable business growth in the digital era.